Analysis of Service Quality and Customer Satisfaction Among Maxim Online Transportation Service Users in Jabodetabek Using Servqual Dimensions - Annisa Nurawalia; Wita Juwita Ermawati; Mushtofa Mushtofa (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of SERVQUAL dimensions and price on customer satisfaction among users of Maxim's online transportation services in the Greater Jakarta area (Jabodetabek). The results indicate that the dimensions of assurance, reliability, and responsiveness have a positive and significant impact on perceived service quality. In contrast, empathy and tangibles do not show significant influence. Additionally, price has a positive and significant effect on customer satisfaction, while overall perceived service quality does not significantly affect satisfaction. These findings suggest that users prioritize reliability, responsiveness, and competitive pricing over physical facilities or personal attention. The implications of this research offer guidance for online transportation companies to focus service improvement strategies on the aspects that most strongly drive customer satisfaction and loyalty.